2017
DOI: 10.12688/f1000research.12278.2
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a virtual education system based on the DeLone and McLean model:  A path analysis

Abstract: The Internet has dramatically influenced the introduction of Background virtual education. Virtual education is a term that involves online education and e-learning. This study was conducted to evaluate a virtual education system based on the DeLone and McLean model. : This descriptive analytical study was conducted using the census Methods method on all the students of the Nursing and Midwifery Department of Alborz University of Medical Sciences who had taken at least one online course in 2016-2017. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…e-marketplace apps created to replace outdated website models.Several previous studies have shown that system quality plays an important role in creating user satisfaction (Lee et al, 2018;Seta et al, 2018). Research conducted to evaluate the campus learning system in Iran found that system quality had the greatest effect on user satisfaction compared to information quality and service quality (Mahmoodi et al, 2017). However, there are still research results that are different from previous findings who found that system quality had no effect on user satisfaction (Pringgandani et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…e-marketplace apps created to replace outdated website models.Several previous studies have shown that system quality plays an important role in creating user satisfaction (Lee et al, 2018;Seta et al, 2018). Research conducted to evaluate the campus learning system in Iran found that system quality had the greatest effect on user satisfaction compared to information quality and service quality (Mahmoodi et al, 2017). However, there are still research results that are different from previous findings who found that system quality had no effect on user satisfaction (Pringgandani et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
“…The previous studies showed that the model had been used for examining the determinants of the success of various information systems, such as online learning systems (OLS), virtual education systems, and electronic health records. [16][17][18] Therefore, a study needs to be carried out to measure the success of PL utilization using the D&M IS Success Model framework. The study is expected to provide beneficial information to the stakeholders to improve the efficacy of implementing information technology applications at the moment and in the future to strengthen the government's and community's resilience during pandemics.…”
Section: Kesmas: Jurnal Kesehatan Masyarakat Nasionalmentioning
confidence: 99%
“…The IS success model has been validated by several previous researchers, [17]and [18], and has been adopted in identifying the factors contributing to the success of e-government implementation with results proven to be valid [19]. Moreover, an internet-based application was used by the users to search and make transactions, therefore, there is a need to provide systems with good qualities for information, system, and services.…”
Section: Hypothesis Model E-government and Updated Dandm Is Success Modelmentioning
confidence: 99%